2018
DOI: 10.1039/c7ra13587d
|View full text |Cite
|
Sign up to set email alerts
|

Iminoxyl radicalsvs. tert-butylperoxyl radical in competitive oxidative C–O coupling with β-dicarbonyl compounds. Oxime ether formation prevails over Kharasch peroxidation

Abstract: The Kharasch peroxidation system Cu(ii)cat./t-BuOOH, the source oft-BuOO˙ radicals, can be switched to generate iminoxyl radicals by adding various oximes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
(131 reference statements)
3
13
0
Order By: Relevance
“…Based on these results, it can be concluded that the oxidative C−H activation of alkyl benzenes and benzyl alcohols to the corresponding benzyl alcohols and aryl aldehydes, respectively, mainly is done in the presence of TBAB and TBHP and finally desired ester will produced via the cross‐dehydrogenative coupling of aryl aldehyde and benzyl alcohol in the presence of NMZI‐CuO‐9 : 1. According to these results and some reports about the generation of radicals with Cu 2+ /TBHP as well as Br − /TBHP systems, we proposed a multistep pathway for the synthesis of esters through the reaction of alkyl benzenes and benzyl alcohols in the presence of NMZI‐CuO‐9 : 1 and TBAB (Scheme ). The addition of butylated hydroxytoluene (BHT) (a strong radical inhibitor) to the model reaction of toluene ( 1 a ) and benzyl alcohol ( 2 a ) completely inhibited the reaction under the optimized reaction conditions.…”
Section: Resultsmentioning
confidence: 69%
“…Based on these results, it can be concluded that the oxidative C−H activation of alkyl benzenes and benzyl alcohols to the corresponding benzyl alcohols and aryl aldehydes, respectively, mainly is done in the presence of TBAB and TBHP and finally desired ester will produced via the cross‐dehydrogenative coupling of aryl aldehyde and benzyl alcohol in the presence of NMZI‐CuO‐9 : 1. According to these results and some reports about the generation of radicals with Cu 2+ /TBHP as well as Br − /TBHP systems, we proposed a multistep pathway for the synthesis of esters through the reaction of alkyl benzenes and benzyl alcohols in the presence of NMZI‐CuO‐9 : 1 and TBAB (Scheme ). The addition of butylated hydroxytoluene (BHT) (a strong radical inhibitor) to the model reaction of toluene ( 1 a ) and benzyl alcohol ( 2 a ) completely inhibited the reaction under the optimized reaction conditions.…”
Section: Resultsmentioning
confidence: 69%
“…radicals by reactions of Cu centres within the [Cu 2 (O 2 CR) 4 ] paddlewheel. [ 1 , 18 , 19 , 20 ] The reactive tert ‐butoxy and tert ‐peroxy derived radicals abstract a hydrogen atom from the benzylic position of the substrate, and the resultant C radical is then converted to the product via O‐transfer. Rietveld refinement of the SPXRD data of t BuOOH‐loaded MFM‐170 confirmed binding of t BuOOH to the vacant metal site within the [Cu 2 (O 2 CR) 4 ] paddlewheel (Figure 2 , Figure S9) with Cu⋅⋅⋅O of 2.840(2) Å.…”
mentioning
confidence: 99%
“…Later, the Cu(BF 4 ) 2 (cat. )/t-BuOOH oxidative system [87] was proposed as an alternative to stoichiometric metal-containing oxidants, such as KMnO 4 , Mn(OAc) 3 , and KMnO 4 /Mn(OAc) 3 (Scheme 16).…”
Section: Methodsmentioning
confidence: 99%